2021
DOI: 10.1177/0193945920982599
|View full text |Cite
|
Sign up to set email alerts
|

Educating Homecare Nurses about Deprescribing of Medications to Manage Polypharmacy for Older Adults

Abstract: The purpose of this study is to evaluate the acceptability, appropriateness, and effectiveness of educational intervention with homecare nurses about deprescribing of medications among older adults. An evaluation research study was conducted using survey design to evaluate deprescribing education with a total sample of 45 homecare nurses from three homecare organizations. Post-training evaluation data were evaluated using Likert scale and open-ended questions were analyzed using descriptive statistical analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
(27 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, their results revealed that educating homecare nurses about effective multi-medication, safe prescribing, and the deprescribing process can be critical for polypharmacy management in parallel with developing technology-enabled home care (24).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, their results revealed that educating homecare nurses about effective multi-medication, safe prescribing, and the deprescribing process can be critical for polypharmacy management in parallel with developing technology-enabled home care (24).…”
Section: Discussionmentioning
confidence: 99%
“…The CHOPPED questionnaire has the potential to be used in primary care settings where other healthcare providers, such as nurses (nurse practitioners’ practices, mobile nursing practices), have prescribing rights or participate in deprescribing. Recently, there has been a surge of research publications regarding nurses’ positions and perspectives in deprescribing, especially in terms of geriatric patients [ 62 , 63 , 64 ]. Depending on the particular nursing professionals’ responsibilities, both versions of CHOPPED could be used.…”
Section: Discussionmentioning
confidence: 99%
“… 33 A follow-up feasibility study by Sun and colleagues in 2021 revealed that home-care nurses are very interested in learning about deprescribing and would like to have tools and protocols that they can use in the home environment when they are engaging in medication reconciliations to help reduce polypharmacy. 34 Further research is needed to implement larger scale education of home-care nurses to address polypharmacy through deprescribing principles and ascertain its effectiveness among homebound patients. Additionally, Sun and colleagues qualitative study results highlight the importance of creating effective means of communication between the home health nurses and the home-based primary-care teams, to help in the process of addressing polypharmacy.…”
Section: Introductionmentioning
confidence: 99%